PERANCANGAN FOTOGRAFI PRODUK UNTUK MASYARAKAT DISABILITAS DI KLATEN - Yulianto, Arif; Susilo, Dahlan; Ruswanti, Diyah (Program Studi Desain Komunikasi Visual, 2025)
The research activity was carried out by involving one PPDK partner, namely the Klaten Disability Association. This study aims to examine the process of designing product photography for the disabled community in Klaten. Every form of work produced from photography has no other purpose and concept of creation that begins with a basic idea that develops into a practical implementation with the support of equipment and techniques of expression through visual language. Furthermore, through experiments and explorations of the target (exposure) and the process of its presence until it becomes the subject matter of the photographic work. The problem faced by the partner is not having knowledge about product photography so that there are no product photos that can be displayed on social media or print media, amidst the tight competition of MSMEs. To overcome this problem, research is needed on partners through the use of product photography with smartphones as an effort to improve the quality of promotion. The purpose of this study is to examine the improvement of partners' abilities in improving product photography design. The method used in this study is the Monroe Breadsley method, which emphasizes the beauty of product photos that sell well. Monroe Beardsley in Problems in the Philosophy of Criticism explains that there are 3 characteristics that make aesthetic objects beautiful, namely: 1) Unity: well-arranged or perfect in shape; 2) Complexity: not very simple, rich in content and elements that contradict each other or contain subtle differences; 3) Seriousness (intensity): having a certain quality that stands out and is not just something empty. The results of this research activity are that there is an increase in the quality of product photos obtained by partners.